Use of immunohistochemistry in the diagnosis of melanocytic lesions: applications and pitfalls. (July 2010) - Ivan, Doina; Prieto, Victor G
The accurate diagnosis of melanocytic lesions is essential for the adequate clinical management of the patients. Besides the histopathologic examination, immunohistochemical studies are often used as an adjunct in distinguishing melanocytic lesions from tumors with different origin or between benign and malignant melanocytic lesions. In the first part of this article, we analyze data on currently used immunohistochemical markers, with special emphasis on their applicability to clinical practice, and underline their potential pitfalls. The pathogenesis of malignant transformation of melanocytes is not completely understood. Recent studies report that various melanoma progression markers are preferentially expressed in benign or malignant melanocytic lesions or show different expression in subsequent stages of tumor development. Furthermore, in recent years, emerging genetic studies suggest that there are distinctive patterns of chromosomal aberrations in different subtypes of melanoma that can be altered by newly developed targeted therapies. In the second part of our article, we will discuss the most significant progression markers in melanoma that can be detected by immunohistochemistry and their potential usefulness for diagnosis, prognosis, staging or as therapeutic targets.